Adolescent undernutrition and early adulthood bone mass in an urbanizing rural community in India. Issue 1 (December 2015) - Matsuzaki, Mika; Kuper, Hannah; Kulkarni, Bharati; Ploubidis, George; Wells, Jonathan; Radhakrishna, Kankipati; Prabhakaran, Poornima; Gupta, Vipin; Walia, Gagandeep; Aggarwal, Aastha; Prabhakaran, Dorairaj; Rameshwar Sarma, K.; et al.
Abstract Summary The long-term effects on bone health of nutritional status in adolescence are unclear. The impact of adolescent and current body mass on bone mass in young adulthood in rural India was assessed. Current lean mass was a more important determinant of bone mass than thinness during adolescence in this population. Purpose/introduction Adolescence is a crucial period for skeletal growth. However, the long-term effects on bone health of nutritional status in adolescence, particularly in the context of nutritional transition, are unclear. The current manuscript assessed the impact of adolescent and current body size on bone mass in young adulthood in an Indian rural community that is undergoing rapid socioeconomic changes. Methods The Andhra Pradesh Children and Parents Study is a prospective cohort study in Hyderabad, India. In 2003–2005, the study collected anthropometric and cardiovascular data on adolescents (mean age = 16 years old). The second and third waves of the study in 2009–2012 collected data on current anthropometric measures, areal bone mineral density (aBMD) in hip and lumbar spine (L1–L4) measured by dual-energy X-ray absorptiometry, and living standards of the trial participants who were now young adults (mean age = 22 years old). Results The median body mass index (BMI) of the 722 participants included in this analysis was 16.8 kg/m2 during adolescence, while the median BMI as young adults was 19.3 kg/m2 . Lower aBMD during adulthood was associated with lower adolescent BMI (β (95 % confidence interval) for hip aBMD 0.017 (0.013 to 0.022) and LS aBMD 0.012 (0.008 to 0.016)). This association was attenuated upon adjustment for current fat and lean mass (β (95 % CI) for hip aBMD 0.00 (−0.005 to 0.005) and LS aBMD 0.005 (0.000 to 0.01)). There was clear evidence for positive associations between aBMDs and current lean mass. Conclusions Current lean mass was a more important determinant of bone mass than thinness during adolescence in this population. Weight gain during late adolescence and young adulthood coupled with improvement in lean mass may help to mitigate any adverse effects that pre-adulthood undernutrition may have on bone mass accrual.